If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2t + t + -6)(2t + 2t + -1) = 0 Reorder the terms: (-6 + 2t + t)(2t + 2t + -1) = 0 Combine like terms: 2t + t = 3t (-6 + 3t)(2t + 2t + -1) = 0 Reorder the terms: (-6 + 3t)(-1 + 2t + 2t) = 0 Combine like terms: 2t + 2t = 4t (-6 + 3t)(-1 + 4t) = 0 Multiply (-6 + 3t) * (-1 + 4t) (-6(-1 + 4t) + 3t * (-1 + 4t)) = 0 ((-1 * -6 + 4t * -6) + 3t * (-1 + 4t)) = 0 ((6 + -24t) + 3t * (-1 + 4t)) = 0 (6 + -24t + (-1 * 3t + 4t * 3t)) = 0 (6 + -24t + (-3t + 12t2)) = 0 Combine like terms: -24t + -3t = -27t (6 + -27t + 12t2) = 0 Solving 6 + -27t + 12t2 = 0 Solving for variable 't'. Factor out the Greatest Common Factor (GCF), '3'. 3(2 + -9t + 4t2) = 0 Factor a trinomial. 3((1 + -4t)(2 + -1t)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(1 + -4t)' equal to zero and attempt to solve: Simplifying 1 + -4t = 0 Solving 1 + -4t = 0 Move all terms containing t to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4t = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4t = 0 + -1 -4t = 0 + -1 Combine like terms: 0 + -1 = -1 -4t = -1 Divide each side by '-4'. t = 0.25 Simplifying t = 0.25Subproblem 2
Set the factor '(2 + -1t)' equal to zero and attempt to solve: Simplifying 2 + -1t = 0 Solving 2 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1t = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1t = 0 + -2 -1t = 0 + -2 Combine like terms: 0 + -2 = -2 -1t = -2 Divide each side by '-1'. t = 2 Simplifying t = 2Solution
t = {0.25, 2}
| 120+12(30)+x=900 | | 9-4m=1 | | 3x-5=8x+5 | | 20x+5=15x+25 | | 4n-12=12n-4 | | 11n=10n+16 | | 2x+58=6x-10 | | -5(3x+4)=4x+16-7x | | 0.3x-0.5x+3=-4 | | -4x-5x= | | 9n-34=6n+5 | | m+(-5)=19 | | 5(x+4)=6(3x-2) | | 4y+xy=11 | | .75a+14=8 | | 2(1-2b)+2(1+5b)=-9+6b | | (x^4)+(41x^2)+400=0 | | 6p+(p-4)=4p | | 264-3x=42x+19 | | -36x^4+25x^3-4= | | h+(-9)=-9 | | (x^4)+(4x^2)+400=0 | | 15t+9=5t+9 | | 5b-12=14 | | 9(x-4)=72 | | -10y-7=6y+9 | | d-15=44 | | -441=4(-8n-4) | | 2(8x+2)=3(2x-7) | | 5x+2x=6x-2 | | 5x-6(3x+4)=9(x-6)+3 | | -9x+4x+15-10x= |